Birth-Associated Neonatal Encephalopathy: Postresuscitation Care in West African Newborns - Enweronu-Laryea, C.C.; Adedemy, J.D.; Okonkwo, I.R.; Lee, A.C.C.; Robertson, N.J. (NeoReviews, 2018)
The West African subregion has the highest burden of neonatal mortality globally and the neonatal mortality rate is decreasing very slowly. A high proportion of newborn deaths are preventable and improved quality of care can reduce long-term morbidity in survivors. Perinatal asphyxia is the major cause of death and disability in term infants in the subregion. Neonatal resuscitation training programs have reduced stillbirths and early neonatal mortality but the overall effect on survival to discharge, population-based perinatal mortality, and long-term impairment is uncertain. Gaps in the health system and quality of postresuscitation care for affected newborns may defeat gains from global efforts to improve care around the time of birth. The aim of this review is to discuss the current situation of postresuscitation care of term infants with presumed birth-associated neonatal encephalopathy in West Africa. Limitations in diagnosing and treating affected infants and feasible interventions to improve acute and postdischarge care are discussed.